Motivación y rendimiento laboral de los trabajadores del Hospital Iquitos “César Garayar García” 2023 - Arbildo Suarez, Mary Isabel (2024)
This research aims to analyze the connection between motivation and work performance of employees of the Iquitos "César Garayar García" hospital in the year 2023. The study was carried out using a basic and quantitative research design approach, using a descriptive and non-experimental cross sectional design. A sample of 168 workers from the aforementioned hospital was chosen to be part of the study. The collected data were subjected to a statistical analysis using SPSS and were organized in tables to describe the levels of correlation of the variables and their respective dimensions, evaluating their values and frequencies. The hypothesis was tested by using Pearson's correlation coefficient, which returned a result of 0.167. Consequently, it was concluded that there is significant relationship between the variables studied at the Iquitos "César Garayar García" hospital in 2023.